An empirical analysis on capital budgeting models, uncertainty tools, cost of capital and firm performance a comparison between australia and sri lanka - Pratheepkanth, P.; Thirunavukarasu, V.; Balaputhiran, S. (University of Jaffna, 2018)
This paper explores how environmental differences in developed and emerging economies affect capital budgeting techniques (CBT) choices and, as a result, influence firm performance. A quantitative-descriptive literature-review analysis provides this two-nation study with an understanding of the underlying forces and issues; which were used to shape the design and content of the questionnaire; which were sent to 300 stock-exchange-listed firms (150 in Australia and 150 in Sri Lanka). Secondary data for 2013-17 are acquiredfrom the ASX, CSE’s websites and are used to compute return on assets, return on equity, Tobin Q, and earnings per share for the sampled firms. Australian firms tend to rely heavily on sophisticated CBTs, relatively small Sri Lankan firms prefer simple analysis techniques, but larger Sri Lankan firms tend to be as adept at sophisticated CBT analysis as Australian firms. Further, while Australian firms have a positive association between their performance and their use of more sophisticated CBTs (Tobin’s Q, excepted), Sri Lankan firms tend to experience a negative association between their performance and their use of more sophisticated CBTs (EPS,excepted). The study adds to the general knowledge on CB practices by showing that the nature of the firm appears to swamp the nurture of the environment in which it is embedded.
Keywords: Capital budgeting practices; Developed market; Firm performance; Emerging market